A BIM-based Dynamic Model for Site Material Supply. (2016) - Yu, Qunzhou; Li, Kaiman; Luo, Hanbin
Abstract: Construction site conditions are dynamic in nature, involving numerous activities and resources scattered on a usually congested site. Planning and availability of material laydown area on construction sites is an essential activity for every project. This paper presents the development of a BIM-based dynamic model for site material supply that is capable of identifying optimal dynamic scheme for the solution of this problem—what (material), how many, when, and where. The method of 4D modelling is investigated, as well as the acquisition method of site information, and the optimal scheme generation method. Contributions include the development of the BIM-based model for site material supply management, and a case study for the process of the site supply scheme implementation.